Three Ones and Aristotle's Metaphysics. (23rd November 2018) - Crager, Adam
Aristotle's Metaphysics defends a number of theses about oneness [ to hen ]. For interpreting the Metaphysics ' positive henology, two such theses are especially important: (1) to hen and being [ to on ] are equally general and so intimately connected that there can be no science of the former which isn't also a science of the latter, and (2) to hen is the foundation [ archē ] of number qua number. Aristotle decisively commits himself to both (1) and (2). The central goal of this article is to improve our understanding of what the Metaphysics ' endorsement of their conjunction amounts to. To this end we explore three manners of being one which enter into Aristotle's Metaphysics : I call them unity, uniqueness, and unit-hood . On the view the article defends, it's unity (and not uniqueness) that's at issue in Aristotle's endorsement of (1) and unit-hood (and not uniqueness) that's at issue in his endorsement of (2). The Metaphysics ' positive henology as whole, I suggest, is best interpreted by positing a theory-internal distinction between unity, uniqueness, and unit-hood.